Healthy lifestyle behaviors and depressive symptoms: a national cross-sectional study of the older adults in China - Jiao, Haojin; Ge-Zhang, Shangjie; Yang, Jingqi (Frontiers in Medicine, 2025)
IntroductionThis investigation assesses the impact of healthy lifestyle behaviors on depressive symptoms among older adults in China, utilizing data from the 2020 China Health and Retirement Longitudinal Study (CHARLS).MethodsThe analysis included 9,020 valid samples from individuals aged 60 and above. Sleep duration, social participation, and physical exercise were examined as independent variables. Depressive symptoms were measured using the CESD-10 scale, with relationships analyzed through an ordered logistic regression model.ResultsThe study reveals significant correlations between healthy lifestyle behaviors — specifically adequate sleep, regular physical exercise, and active social participation — and reduced prevalence of depressive symptoms in the elderly (p < 0.05).DiscussionThese findings underscore the potential of healthy lifestyle interventions as key strategies in alleviating the mental health burden among China’s aging population. Integration of these results into public health policies is recommended to enhance the mental well-being of older adults.